2019
DOI: 10.1101/701706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic rescue without genomic swamping in wild populations

Abstract: 22Gene flow is an enigmatic evolutionary force because it can limit adaptation but can also 23 help populations escape inbreeding depression. Manipulating gene flow for conservation 24 purposes is a controversial, but potentially powerful management strategy. We use 25 multigenerational pedigrees and genomics to test demographic and evolutionary 26 consequences of manipulating gene flow in two isolated wild Trinidadian guppy 27 populations. We found that on average, hybrids lived longer and reproduced more.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Studies of selection in contemporary hybridizing populations offer another route to merge pattern and process, and to tease apart forms of selection acting in admixed populations. For example, Chen et al, 2019 ; Chen et al, 2016 and Fitzpatrick, 2019 studied weakly differentiated populations and found that genome-wide selection broadly favored ancestry derived from migrants in small populations, consistent with the idea that in small populations foreign ancestry can be favored to lighten the genetic load. In contrast, we recently found little evidence that hybridization load shapes genome-wide ancestry in hybrid swordtail populations formed between species with substantial differences in historical effective population size ( Schumer et al, 2018 ).…”
Section: Ways Forwardmentioning
confidence: 53%
“…Studies of selection in contemporary hybridizing populations offer another route to merge pattern and process, and to tease apart forms of selection acting in admixed populations. For example, Chen et al, 2019 ; Chen et al, 2016 and Fitzpatrick, 2019 studied weakly differentiated populations and found that genome-wide selection broadly favored ancestry derived from migrants in small populations, consistent with the idea that in small populations foreign ancestry can be favored to lighten the genetic load. In contrast, we recently found little evidence that hybridization load shapes genome-wide ancestry in hybrid swordtail populations formed between species with substantial differences in historical effective population size ( Schumer et al, 2018 ).…”
Section: Ways Forwardmentioning
confidence: 53%
“…Potential concerns about outbreeding depression and/or genomic swamping of the AENP buffalo population following this proposed genetic supplementation could be alleviated by considering the current support for an estimated short time since isolation (~100 years) [ 17 , 49 ] and by conducting regular genetic monitoring of the population. Furthermore, recent studies showed local genes, and alleles related to local adaptation, were maintained in the recipient population after genetic supplementation, while the benefits of genetic rescue were still observed [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether characterized using reduced-representation sequence data or whole-genome sequence (WGS) data, SNP-based estimates of genome-wide diversity are being used to better inform conservation by delineating species (e.g., Quattrini et al, 2019;but see Stanton et al, 2019), detecting hybridisation and introgression (Dufresnes & Dubey, 2020;Peters et al, 2016; but see Forsdick et al, 2021 preprint;Hauser, Athrey, & Leberg, 2021 preprint), identifying conservation units (e.g., Liddell et al, 2020), identifying source populations for conservation translocations (e.g., Dresser, Ogle, & Fitzpatrick, 2017), and guiding conservation breeding programs (e.g., Galla et al, 2020;Wright et al, 2020). Beyond genome-wide diversity, there is a growing consensus around the importance of considering functional genomic diversity in conservation management (Fitzpatrick et al, 2020;Hoelzel, Bruford, & Fleischer, 2019;S. Li et al, 2014;Willi, Van Buskirk, & Hoffmann, 2006).…”
Section: Structural Variants: a New Tool In The Conservation Genomics Toolboxmentioning
confidence: 99%